Zinc ion battery gel electrolyte and preparation method and application thereof
By preparing a dual-network gel electrolyte in a zinc ion battery, the problems of low ionic conductivity and poor electrochemical activity of gel electrolyte in the prior art are solved, and higher mechanical properties, corrosion resistance and electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411785672.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing zinc ion battery gel electrolytes have problems with low ionic conductivity and poor electrochemical activity, which limits the charge and discharge rate and overall performance of the battery.
By adding propylene derivatives, cellulose and inorganic nanoparticles to the electrolyte solution, and after stirring, defoaming and thermal polymerization, gel electrolyte with a dual network structure was prepared.
It improves the mechanical properties and corrosion resistance of gel electrolytes, enhances ion conductivity and ion migration number, and significantly improves the cycling stability and electrochemical performance of zinc ion batteries.
Smart Images

Figure CN119684525A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to a zinc ion battery gel electrolyte and a preparation method and application thereof. Background Art
[0002] In the face of increasingly severe energy crisis and environmental pollution problems, the development of renewable energy and its energy storage technology has become particularly urgent. Lithium-ion batteries have been widely used in consumer electronics, transportation and other fields due to their high energy density and cycle stability. However, lithium-ion batteries are currently facing problems such as high cost, low safety, and lithium resource collapse, which has led researchers to look for alternatives to lithium-ion batteries. Aqueous zinc-ion batteries have attracted widespread attention due to their low cost, high safety, environmental friendliness and abundant zinc resources.
[0003] Although aqueous zinc-ion batteries have many advantages, there are still some problems that hinder their large-scale application. In particular, the zinc negative electrode has serious side reactions such as dendrite growth, hydrogen evolution, corrosion and passivation in aqueous liquid electrolytes, which have a serious impact on the life of the battery and there is a risk of leakage. Gel electrolytes are usually composed of a polymer matrix and a solution containing electrolyte salts. They are an electrolyte between liquid and solid. The polymer matrix forms a three-dimensional network structure, and its internal pore structure can lock the liquid electrolyte, effectively avoiding the leakage of the liquid electrolyte. At the same time, it improves the zinc negative electrode-electrolyte interface, changes the solid-liquid interface to a solid-solid interface, avoids direct contact between water and the zinc negative electrode, and effectively solves the problems of zinc dendrites and interface side reactions. Therefore, gel electrolytes have ample development prospects in realizing the large-scale application of zinc-ion batteries.
[0004] However, existing gel electrolytes, such as polyacrylamide, polyvinyl alcohol, polyethylene oxide, xanthan gum, gelatin, sodium alginate, etc., all have problems such as low ionic conductivity and poor electrochemical activity. -4 ~10 -1 S / cm, which is lower than that of liquid electrolytes, limiting the charge and discharge rate and overall performance of the battery. Therefore, it is of great significance to design and develop a gel electrolyte that meets the application requirements of zinc-ion batteries.
[0005] Patent CN118281372A discloses a cellulose / sodium alginate composite gel electrolyte membrane and a preparation method thereof, wherein cellulose and sodium alginate are mixed and aged to obtain a composite hydrogel, which is then freeze-dried and immersed in an electrolyte solution to obtain a composite gel electrolyte membrane. The obtained electrolyte has good stability, liquid retention capacity and ion conductivity, but the above method requires freeze drying, which is a complex process, and requires immersion in an electrolyte for ion exchange, which increases time costs.
[0006] Patent CN118772445A discloses a modified hydrogel electrolyte for quasi-solid-state zinc ion battery and its preparation method. By introducing tetramethyl urea into polyvinyl alcohol, the mechanical properties and corrosion resistance of the electrolyte are improved, so that the electrolyte material can better resist physical stress and chemical corrosion during use, thereby extending the service life of the battery. However, the organic zinc salt used in the gel electrolyte prepared by the patent is expensive and costly, which is not conducive to actual production.
[0007] Patent TWI750909 (B) discloses a hydrogel, a preparation method thereof, a hydrogel electrolyte, a supercapacitor and a battery. The preparation method of the hydrogel electrolyte comprises the following steps: (1) using tetraethoxysilane and vinyltriethoxysilane as raw materials to react in ammonia water to prepare vinyl silicon nanoparticles, then adding (N,N-dimethyl-3-aminopropyl)trimethoxysilane, and drying in argon to prepare zwitterion surface inorganic nanoparticles; (2) mixing the zwitterion surface inorganic nanoparticles prepared in step (1) with sulfobetaine, and deoxygenating with nitrogen to obtain solution A; (3) adding ammonium persulfate to solution A, heating and polymerizing to obtain a gel electrolyte. The invention introduces inorganic nanoparticles treated with zwitterion surface into the zwitterion polymer skeleton to achieve high mechanical strength, widen the electrochemical window, increase ionic conductivity and inhibit self-discharge rate. However, the preparation method provided by the technical solution has a cumbersome process, a complex process, requires inert gas protection, is costly, and is not conducive to actual production.
[0008] Patent US11942598 (B2) discloses an ionic liquid softened polymer electrolyte for zinc ion batteries. Ionic liquid, nano zinc oxide, polyethylene oxide and organic zinc salt are mixed and an electrolyte film is prepared by hot pressing. The invention uses ionic liquid as a plasticizer and adds nano zinc oxide filler to increase the non-crystalline phase in polyethylene oxide, thereby improving the ionic conductivity and mechanical properties of the electrolyte. However, the ionic conductivity of the polymer electrolyte prepared by the patent is low, only 0.5×10 -4 S / cm, which is much lower than that of liquid electrolytes and can hardly meet the application requirements of zinc-ion batteries.
[0009] Therefore, providing a gel electrolyte with simple process, excellent electrochemical properties, good mechanical properties, high efficiency and stability has broad application prospects. Summary of the invention
[0010] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a zinc ion battery gel electrolyte.
[0011] Another object of the present invention is to provide a zinc ion battery gel electrolyte.
[0012] Another object of the present invention is to provide application of the above-mentioned gel electrolyte in zinc ion batteries.
[0013] Another object of the present invention is to provide a zinc ion battery.
[0014] The purpose of the present invention is achieved through the following technical solutions:
[0015] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0016] (1) adding a propylene derivative and cellulose to an electrolyte solution and stirring the mixture to obtain a solution A;
[0017] (2) adding inorganic nanoparticles to solution A and dispersing them evenly to obtain solution B;
[0018] (3) Adding an initiator and a cross-linking agent to solution B, stirring evenly, removing bubbles, and placing the solution in a mold for polymerization to obtain a zinc ion battery gel electrolyte.
[0019] Preferably, the inorganic nanoparticles are one or more of nano-silicon dioxide, nano-aluminum oxide, nano-zinc oxide, nano-zirconium oxide or nano-titanium dioxide.
[0020] Preferably, the addition amount of the inorganic nanoparticles is 0.1-10% of the mass of the propylene derivative, preferably 0.5-5%, and more preferably 0.5-2.5%.
[0021] Preferably, the propylene derivative is one or more of acrylic acid, acrylamide, and methyl acrylate;
[0022] The cellulose is one or more of carboxymethyl cellulose, methyl cellulose and hydroxyethyl methyl cellulose, and the added amount of the cellulose is 1-10% of the mass of the propylene derivative.
[0023] Preferably, the electrolyte solution is a zinc salt solution, the zinc salt is one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or zinc trifluoromethanesulfonate, and the concentration of the electrolyte solution is 1 to 5 mol / L;
[0024] The cross-linking agent is one of N,N'-methylenebisacrylamide, polyethylene glycol or N,N'-bis(acryl)cystamine;
[0025] The initiator is ammonium persulfate or potassium persulfate.
[0026] Preferably, the degassing in step (2) is vacuum degassing, and the degassing time is 0.1 to 0.5 hours;
[0027] The polymerization in step (3) is thermal polymerization, the polymerization temperature is 40 to 90° C., and the polymerization time is 0.5 to 3 hours.
[0028] Preferably, the concentration of the propylene derivative in the solution A in step (1) is 100 to 500 g / L, preferably 200 g / L;
[0029] The initiator concentration in the solution B is 0.2-3 g / L, preferably 2 g / L, and the cross-linking agent concentration is 1-4 g / L, preferably 4 g / L.
[0030] A zinc ion battery gel electrolyte is prepared by the above method.
[0031] Preferably, the zinc ion battery gel electrolyte is composed of a double network structure polymer matrix, inorganic nanoparticles and an electrolyte solution, wherein the double network structure polymer matrix is a three-dimensional network skeleton with a polymer of a propylene derivative as the main body and cellulose as the guest network skeleton, and the zinc ion battery gel electrolyte fixes the electrolyte solution inside the gel.
[0032] Preferably, the zinc ion battery gel electrolyte comprises, by mass percentage: 10-15% propylene derivative, 1-1.5% cellulose, 0.05-0.75% inorganic nanoparticles, 0.20-0.30% initiator, 0.10-0.15% crosslinking agent, and the balance is electrolyte solution.
[0033] Application of the above gel electrolyte in zinc ion batteries.
[0034] A zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the zinc ion battery gel electrolyte.
[0035] Preferably, the positive electrode comprises a manganese-based compound, and the negative electrode is a zinc sheet.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] (1) Improve the mechanical properties and corrosion resistance of gel electrolyte
[0038] The present invention introduces a guest network carboxymethyl cellulose into the main three-dimensional network skeleton of acrylamide to construct a gel with a double network structure. The double network structure polymer matrix can effectively enhance the interaction between molecules, provide good mechanical strength, and have better mechanical properties than a single network gel electrolyte. The assembled battery has a smaller corrosion current, showing that it has better corrosion resistance. The carboxyl groups on the carboxymethyl cellulose can guide the migration of zinc ions and reduce the activity of water, thereby achieving uniform deposition of zinc ions, inhibiting the growth of zinc dendrites on the zinc negative electrode, and increasing the cycle stability of the zinc negative electrode. The current density is 1 mA / cm 2、Area capacity is 1mAh / cm 2 Under the conditions of , the assembled metal zinc / / electrolyte / / metal zinc battery can be stably cycled for more than 1000 hours with a current density of 5mA / cm 2 、Area capacity is 1mAh / cm 2 Under the conditions of high efficiency, it can still cycle stably for 400 hours, making it a highly safe, efficient and stable gel electrolyte.
[0039] (2) Improve the ionic conductivity and ion migration number of gel electrolytes
[0040] The present invention introduces inorganic nanoparticles, which, on the one hand, increase the amorphous region in the polymer, promote the segmental movement of the polymer, and improve the ionic conductivity of the gel electrolyte; on the other hand, the space charge layer spontaneously formed at the interface between the inorganic particles and the polymer matrix can provide a fast channel for the transmission of zinc ions, thereby increasing the ion migration number, and the obtained gel electrolyte has excellent electrochemical properties.
[0041] (3) The preparation method is simple, the raw materials are readily available, and it is suitable for large-scale production
[0042] The raw materials required for the high-safety gel electrolyte of the present invention are easily available and widely sourced, and the preparation method is simple and easy. The electrolyte solution is fixed inside the gel by direct polymerization in a salt solution, and there is no need to immerse it in a salt solution for a long time for ion exchange, thereby shortening the preparation time, having high production efficiency, and being suitable for large-scale production and practical application promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Nyquist plots of stainless steel / / electrolyte / / stainless steel cells assembled with electrolytes prepared in Examples 1-6 and Comparative Examples 1-3.
[0044] Figure 2 Nyquist plots of metal zinc / / electrolyte / / metal zinc batteries assembled with electrolytes prepared in Examples 1-6 and Comparative Examples 1-3.
[0045] Figure 3 The tensile stress-strain curves of the electrolytes prepared in Example 2 and Comparative Example 1.
[0046] Figure 4 The Tafel curves of the electrolytes prepared in Example 2 and Comparative Example 1 are measured.
[0047] Figure 5 The metal zinc / / electrolyte / / metal zinc battery assembled with the electrolyte prepared in Example 2 and Comparative Example 1 was charged at a current density of 1 mA / cm 2 、Area capacity is 1mAh / cm 2 Cycle test diagram under the conditions of .
[0048] Figure 6 The metal zinc / / electrolyte / / metal zinc battery assembled with the electrolyte prepared in Example 2 and Comparative Example 1 was charged at a current density of 5 mA / cm 2 、Area capacity is 1mAh / cm 2 Cycle test diagram under the conditions of .
[0049] Figure 7 The metal zinc / / electrolyte / / metal zinc battery assembled with the electrolyte prepared in Example 2 and Comparative Example 1 was charged at a current density of 1 mA / cm 2 、Area capacity is 1mAh / cm 2 Microscopic morphology of the zinc anode under a scanning electron microscope after 100 charge and discharge cycles under conditions.
[0050] Figure 8 Specific capacity diagram of metal zinc / / electrolyte / / MnO2 batteries assembled with electrolytes prepared in Example 2 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0051] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0052] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0053] Example 1
[0054] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0055] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 1mol / L zinc sulfate in sequence and stirred thoroughly. Then 10mg of nano-titanium dioxide was added and stirred until the mixture was uniformly mixed. The amount added was 0.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0056] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0057] Example 2
[0058] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0059] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 1mol / L zinc sulfate in sequence and stirred thoroughly. Then 30mg of nano-titanium dioxide was added and stirred until the mixture was uniform. The amount added was 1.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0060] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0061] Example 3
[0062] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0063] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 1mol / L zinc sulfate in sequence and stirred thoroughly. Then 50mg of nano-titanium dioxide was added and stirred until the mixture was uniformly mixed. The amount added was 2.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0064] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0065] Example 4
[0066] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0067] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 1mol / L zinc sulfate in sequence and stirred thoroughly. Then 10mg of nano zinc oxide was added and stirred until the mixture was uniform. The amount added was 0.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0068] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0069] Example 5
[0070] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0071] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 1mol / L zinc sulfate in sequence and stirred thoroughly. Then 10mg of nano-silicon dioxide was added and stirred until the mixture was uniform. The amount added was 0.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0072] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0073] Example 6
[0074] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0075] 2g acrylamide and 0.2g carboxymethyl cellulose were added to 10mL of a solution containing 2mol / L zinc sulfate in sequence and stirred thoroughly. Then 10mg of nano-titanium dioxide was added and stirred until the mixture was uniformly mixed. The amount added was 0.5% of the mass of the monomer acrylamide. Then 40mg of N,N'-methylenebisacrylamide and 20mg of potassium persulfate were added and stirred to obtain a uniformly mixed suspension, which was then vacuumed to remove bubbles.
[0076] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0077] Comparative Example 1
[0078] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0079] 2 g of acrylamide was added to 10 mL of a solution containing 1 mol / L zinc sulfate and stirred thoroughly until the mixture was uniformly mixed. Then 40 mg of N,N'-methylenebisacrylamide and 20 mg of potassium persulfate were added and stirred to obtain a uniformly mixed solution, which was then vacuumed to remove bubbles.
[0080] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0081] Comparative Example 2
[0082] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0083] 2 g of acrylamide and 0.2 g of carboxymethyl cellulose were added to 10 mL of a solution containing 1 mol / L zinc sulfate and stirred thoroughly until the mixture was uniformly mixed. Then 40 mg of N,N'-methylenebisacrylamide and 20 mg of potassium persulfate were added and stirred to obtain a uniformly mixed solution, which was then vacuumed to remove bubbles.
[0084] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0085] Comparative Example 3
[0086] A method for preparing a zinc ion battery gel electrolyte comprises the following steps:
[0087] 2 g acrylamide, 0.2 g carboxymethyl cellulose, and 30 mg trisodium citrate were sequentially added to 10 mL of a solution containing 1 mol / L zinc sulfate and stirred thoroughly until the mixture was uniformly mixed. Then 40 mg N,N'-methylenebisacrylamide and 20 mg potassium persulfate were added and stirred to obtain a uniformly mixed solution, which was then vacuumed to remove bubbles.
[0088] The suspension was poured into a mold and heated at 70° C. for 2 hours to initiate monomer polymerization to obtain a gel electrolyte.
[0089] Application Examples
[0090] A method for preparing a zinc ion battery comprises the following steps:
[0091] (1) Preparation of positive electrode materials:
[0092] Dissolve 0.1molKMnO4 and 0.15molMn(CH3COO)2·4H2O in 100mL deionized water. Slowly add Mn(CH3COO)2 solution to KMnO4 solution at room temperature and stir for 4h. Then, wash the solution with deionized water and anhydrous ethanol three times by centrifugation to obtain a brown-black precipitate, which is vacuum dried at 80℃ for 10 hours to obtain the final product MnO2.
[0093] (2) Preparation of positive electrode sheet:
[0094] The positive electrode material, carbon nanotubes and polyvinylidene fluoride were dispersed in an N-methylpyrrolidone solution at a mass ratio of 7:2:1 to form a uniform suspension, which was coated on stainless steel by a doctor blade method and vacuum dried at 60°C for 3 hours to obtain a positive electrode sheet.
[0095] (3) Preparation of full battery:
[0096] The MnO2 positive electrode sheet, gel electrolyte and metal zinc negative electrode were assembled into a full battery, and charge and discharge tests were carried out.
[0097] Performance Testing
[0098] Assemble stainless steel / / electrolyte / / stainless steel symmetric cells and measure electrochemical impedance spectroscopy (EIS) using an electrochemical workstation (CS2350M) with a frequency range of 10 -2 ~106 Hz, the ionic conductivity is calculated using the following formula
[0099]
[0100] In Formula 1, L is the thickness of the gel electrolyte, R is the battery impedance, and S is the electrode area.
[0101] Figure 1 Nyquist plots of stainless steel / / electrolyte / / stainless steel batteries assembled with the electrolytes prepared in Examples 1-6 and Comparative Examples 1-3, where the intersection of the curve and the horizontal axis is the battery impedance.
[0102] Assemble a metal zinc / / electrolyte / / metal zinc battery, measure the impedance and response current of the symmetrical battery before and after polarization, and calculate the zinc ion migration number using the following formula:
[0103]
[0104] In formula 2, I o is the initial response current, R o is the initial impedance, I s is the steady-state current, R s is the steady-state impedance and ΔV is the polarization voltage.
[0105] Figure 2 Nyquist plots of metal zinc / / electrolyte / / metal zinc batteries assembled in Examples 1-6 and Comparative Examples 1-3. The ionic conductivity and zinc ion transference number of Examples 1-6 and Comparative Examples 1-3 calculated by Formula 1 and Formula 2 are shown in Table 1.
[0106] Table 1
[0107] Ionic conductivity (mS / cm) Zinc ion migration number Example 1 31.0 0.54 Example 2 32.6 0.63 Example 3 28.2 0.50 Example 4 14.9 0.67 Example 5 20.5 0.37 Example 6 45.5 0.22 Comparative Example 1 10.1 0.33 Comparative Example 2 19.9 0.47 Comparative Example 3 26.7 0.34
[0108] As shown in Table 1, the ionic conductivity and zinc ion migration number of the gel electrolyte can be improved by adding different nanoparticles, but different nanoparticles have different effects on the electrochemical properties of the gel electrolyte; when the amount of the added nanoparticles is the same, the ionic conductivity of Example 1 with the addition of nano-titanium dioxide is 31.0mS / cm, which is higher than 14.9mS / cm of Example 4 with the addition of nano-zinc oxide and 20.5mS / cm of Example 5 with the addition of nano-silicon dioxide. This is because nano-titanium dioxide can provide more ion channels and increase the ionic conductivity of the electrolyte. Different nanoparticle contents also affect the performance of the electrolyte. The ionic conductivity that can be increased by adding a small amount is limited, and a large amount of addition may cause the agglomeration of nanoparticles, resulting in uneven particle distribution, which is not conducive to the transfer of ions. By comparing Examples 1-5, it can be seen that when the added particles are nano-titanium dioxide and the added amount is 1.5% of the monomer mass, Example 2 has the best electrochemical performance, with an ionic conductivity of 32.6mS / cm and a zinc ion migration number of 0.63, and has the best electrochemical performance.
[0109] The samples were made into dumbbell shapes, and the breaking strength and breaking elongation of the gel electrolytes prepared in Example 2 and Comparative Example 1 were tested using an electronic universal material testing machine. The tensile stress-strain curves are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that the fracture strength of the double network gel electrolyte prepared in Example 2 is as high as 40.85 kPa, which is much higher than 3.80 kPa of the single network gel electrolyte prepared in Comparative Example 1. At the same time, the double network gel electrolyte prepared in Example 2 also has a fracture elongation of 434%, showing excellent mechanical properties.
[0110] Example 2 and Comparative Example 1 were assembled into a metal zinc / / electrolyte / / metal zinc symmetric battery, and Tafel test was performed on it using an electrochemical workstation. The test results are as follows Figure 4 As shown, the battery assembled with the gel electrolyte prepared in Example 2 has a smaller corrosion current than the battery assembled with the single network gel electrolyte prepared in Comparative Example 1, indicating that it has better corrosion resistance.
[0111] The electrolytes prepared in Comparative Example 1 and Example 2 were assembled into metal zinc / / electrolyte / / metal zinc batteries and the current density was 1 mA / cm 2 、Area capacity is 1mAh / cm 2 and current density 5mA / cm 2 、Area capacity is 1mAh / cm 2 The battery cycle performance was tested at room temperature. Figure 5 and Figure 6 shown.
[0112] from Figure 5 It can be seen that at a current density of 1 mA / cm 2 、Area capacity is 1mAh / cm 2 Under the conditions, the battery using comparative example 1 failed in less than 400 hours, and the positive and negative electrodes of the battery expanded and disconnected, and the voltage increased beyond the range. The battery using example 2 showed excellent cycle stability and stable cycle for more than 1000 hours. Figure 6 It can be seen that when using a higher current density (current density 5mA / cm 2 、Area capacity is 1mAh / cm 2 ) was cycled, the battery using Example 2 could still cycle stably for 400 hours, while the battery using Comparative Example 1 short-circuited after 125 hours of cycling. Further, in order to prove that the gel electrolyte constructed by the present invention inhibits dendrite growth, the surface of the zinc negative electrode after cycling was characterized by scanning electron microscopy, and the results are as follows: Figure 7 As shown, the surface flatness of the zinc negative electrode of Comparative Example 1 is poor, and a large number of zinc dendrites are found. By comparing with the comparative example, it can be seen that the gel electrolyte constructed by the present invention can effectively inhibit the growth of zinc dendrites, reduce parasitic reactions competing with zinc deposition, and achieve more uniform zinc deposition during battery cycling.
[0113] Metal zinc / / electrolyte / / MnO2 batteries were assembled and charged and discharged at room temperature at a current density of 1A / g with a cut-off voltage range of 0.5 to 1.9V. The test results are as follows: Figure 8 As shown. Figure 8 It can be seen that the battery assembled with the gel electrolyte prepared in Example 2 of the present invention has a high specific capacity of 185mAh / g in the first discharge, while the battery assembled with the single network gel electrolyte prepared in Comparative Example 1 has a specific capacity of only 172mAh / g in the first discharge; the battery assembled with the gel electrolyte in Example 2 still has a specific capacity of 116mAh / g after 500 cycles, while the battery assembled with the single network gel electrolyte has a rapid capacity decay and a short circuit occurs when the cycle is less than 200 cycles, and the battery fails. This is mainly because compared with Comparative Example 1, the electrolyte in Example 2 has higher ionic conductivity, higher zinc ion migration number, and better mechanical properties, which can significantly improve the cycle performance of aqueous zinc ion batteries.
[0114] The above embodiments are only descriptions of the preferred implementation modes of the present invention. The implementation scope of the present invention is not limited by the above embodiments. Without departing from the design spirit of the present invention, any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a zinc ion battery gel electrolyte, characterized in that: The following steps are involved: (1) adding a propylene derivative and cellulose to an electrolyte solution and stirring the mixture to obtain a solution A; (2) adding inorganic nanoparticles to solution A and dispersing them evenly to obtain solution B; (3) Adding an initiator and a cross-linking agent to solution B, stirring evenly, removing bubbles, and placing the solution in a mold for polymerization to obtain a zinc ion battery gel electrolyte.
2. The method for preparing a zinc ion battery gel electrolyte according to claim 1, wherein The inorganic nanoparticles are one or more of nano silicon dioxide, nano aluminum oxide, nano zinc oxide, nano zirconium oxide or nano titanium dioxide.
3. The preparation method of zinc ion battery gel electrolyte according to claim 1, characterized in that, The added amount of the inorganic nanoparticles is 0.1 to 10% of the mass of the propylene derivative.
4. The method for preparing a zinc ion battery gel electrolyte according to claim 1, wherein The propylene derivative is one or more of acrylic acid, acrylamide and methyl acrylate; The cellulose is one or more of carboxymethyl cellulose, methyl cellulose and hydroxyethyl methyl cellulose, and the added amount of the cellulose is 1-10% of the mass of the propylene derivative.
5. The method for preparing a zinc ion battery gel electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte solution is a zinc salt solution, wherein the zinc salt is one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc acetate or zinc trifluoromethanesulfonate, and the concentration of the electrolyte solution is 1 to 5 mol / L; The cross-linking agent is one of N,N'-methylenebisacrylamide, polyethylene glycol or N,N'-bis(acryl)cystamine; The initiator is ammonium persulfate or potassium persulfate.
6. The method for preparing a zinc ion battery gel electrolyte according to claim 5, wherein: The degassing in step (2) is vacuum degassing, and the degassing time is 0.1 to 0.5 hours; The polymerization in step (3) is thermal polymerization, the polymerization temperature is 40 to 90° C., and the polymerization time is 0.5 to 3 hours.
7. The method for preparing a zinc ion battery gel electrolyte according to claim 1, characterized in that: The concentration of the propylene derivative in the solution A of step (1) is 100 to 500 g / L; The initiator concentration in the solution B is 0.2-3 g / L, and the cross-linking agent concentration is 1-4 g / L.
8. A zinc ion battery gel electrolyte, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the gel electrolyte according to claim 8 in a zinc ion battery.
10. A zinc ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the zinc ion battery gel electrolyte according to claim 8.
Citation Information
Patent Citations
Ionic liquid softened polymer electrolyte for zinc ion batteries
US11942598B2
Gel electrolyte with cellular network structure and preparation method thereof
CN105655636A
Inorganic composite hydrogel electrolyte membrane and preparation and application thereof in aqueous zinc ion battery
CN113921793A
Preparation method of high-strength high-temperature-resistant flexible gel electrolyte
CN115678049A
Method for rapidly preparing gel electrolyte through controllable polymerization mechanism
CN115692874A
Cited By
Acidic corrosion-resistant gel electrolyte as well as preparation method and application thereof
CN121618074A
Fully degradable implantable aqueous zinc ion battery, preparation method and application
CN121709734A
Preparation method of electrolyte for semi-solid zinc-bromine battery, semi-solid zinc-bromine battery and preparation method of semi-solid zinc-bromine battery
CN121839782A
A method for preparing an electrolyte for a semi-solid zinc-bromine battery, a semi-solid zinc-bromine battery, and the method for preparing the same.
CN121839782B